Age Structure Transition in Nepal - Khadka, Samir; Pandit, Dirgha Raj (Journal of Jayaprithvi Multiple Campus, 2025)
This research article examines the age structure transition in Nepal, a nation that has experienced significant demographic changes over the past few decades. Utilizing data from various demographic and health surveys, censuses, and scholarly articles, this paper analyzes the factors contributing to these shifts and their implications for Nepal’s socio-economic development. The study highlights the trends in fertility, mortality, literacy, life expectancy population growth and broad age structure of population. It also discusses the potential policy responses needed to address the challenges and opportunities presented by these demographic changes.